Callus cultures: an alternative research tool to study regulatory mechanisms od carotenoid biosynthesis - Mohd Zaifuddin, Fatimah Azzahra; Othman, Rashidi; Mohd Hassan, Norazian (2013)
Every single step happened in the carotenoid biosynthetic pathway in the leaves is regulated by respective genes. It was presumed that these genes would be inherited by the undifferentiated cells (callus) since they were initiated from the intact plants. Thus, the callus is most likely to develop and respond to internal and external stimuli exactly as the intact plants. Therefore, this study was aimed at establishing callus cultures as an alternative research tool to study the regulatory mechanisms of the carotenoid biosynthesis in plants through a controlled environment. Via HPLC analysis, it was found that different strain of callus cultures accumulated different types of carotenoids as compared to intact plants. The finding from this study suggested that researchers would be able to assess what are the key factors which involved in regulatory mechanisms of individual carotenoid biosynthesis in a particular biology system. Thereafter, future exploration and manipulation of the genetic make-up is made possible to enhance or enrich certain individual carotenoid in food crops.